Mitochondrial Metabolism: Yin and Yang for Tumor Progression. (October 2017) - Valcarcel-Jimenez, Lorea; Gaude, Edoardo; Torrano, Veronica; Frezza, Christian; Carracedo, Arkaitz
Abstract : Altered metabolism is a distinct feature of cancer cells. During transformation, the entire metabolic network is rewired to efficiently convert nutrients to biosynthetic precursors to sustain cancer cell growth and proliferation. Whilst the molecular underpinnings of this metabolic reprogramming have been described, its role in tumor progression is still under investigation. Importantly, the mitochondrion is a central actor in many of the metabolic processes that are altered in tumors. Yet, we have only begun to understand the dualities of mitochondrial function during cancer metastasis and therapy resistance. Paradoxically, mitochondrial metabolism can be both advantageous and detrimental to these processes, highlighting the need for a better understanding of the molecular and microenvironmental cues that define the role of this fascinating organelle. In this review article, we present an updated view on the different mitochondrial metabolic strategies adopted by cancer cells to overcome the many hurdles faced during tumor progression. Trends: Dysregulated metabolism is a distinct feature of cancer. Metabolism adapts during tumor progression to enable cancer cell survival and/or proliferation in an ever-changing microenvironment. Mitochondrial metabolism is a key determinant of tumor progression by impacting on functions such as epithelial-to-mesenchymal transition. Mitochondrial metabolism and derived oncometabolites shape the epigenetic landscape to alter aggressiveness features of cancer cells. Mitochondrial metabolism supports or opposes metastatic dissemination on the basis of the tissue of origin and potentially on the mutational background of the tumor. The redox status imposes a strong selective pressure for the survival of disseminated tumor cells, and mitochondrial metabolism can counteract this stress with the production of antioxidant molecules. Changes in mitochondrial metabolism are relevant for the survival of tumors in response to therapy.